TINJAUAN YURIDIS TANGGUNG JAWAB PENGEMUDI DAN PERUSAHAAN ANGKUTAN ATAS DALAM PENGANGKUTAN BARANG MELALUI ANGKUTAN DARAT (Studi CV. Belawan Indah) - Jinner Sidauruk; Grace M. C. Lumbantobing (Magister Hukum Universitas HKBP Nommensen, 2021)
CV Belawan Indah as a company engaged in the field of freight services is also not free from problems arising from mistakes of drivers and transport companies. In discussing the problems in this thesis needed a method of data collection, to obtain data with research. The research in question is the research method of library research and interviews that is collecting material obtained from primary data and secondary data. The data obtained will be analyzed normatively which is descriptive qualitative so that it illustrates the reality. Based on research results obtained at CV. Belawan Indah that the driver and the transport company are jointly responsible by disadvantage arising in the freightage via truck transportation to delays, damage, and lose the goodsin each operation of transportation and efforts of the owner of the disadvantage in the freightage the goods can file a claim for compensation through a consumer and business dispute resolution agency or the so-called BPSK or through a court of law within the general court.